Simple spectrophotometric methods for the determination of amlodipine and atorvastatin in bulk and tablets - Imad Osman Abu Reid; Hind Mohamed Farid; Sara Osman Eltayeb (SpringerOpen, 2021)
Abstract Background Simultaneous spectrophotometric determination of samples containing more than one analyte presents analytical challenge; the choice of an analytical procedure is strictly related to the extent of overlapping between the individual absorption peaks of these components; if the absorption peaks are satisfactorily resolved, the determination is not problematic, but if the individual component signals are partly or totally overlapped, then powerful techniques are needed. Combined amlodipine and atorvastatin are typical example where special techniques are needed to resolve bands overlapping. Results Application of multiwavelength regression and absorbance factor methods to the analysis of atorvastatin and amlodipine combination proved to be satisfactorily capable of accurate and precise determination of the two analytes. The two methods recoveries were very close to the expected analytes concentrations, and the precision of the methods was < 2% relative standard deviation. Statistical comparison indicated that there is no significant difference between the assay results obtained by the two method as the calculated t values 0.91 and 1.13 for amlodipine and atorvastatin, respectively, were less than the tabulated t value 2.23 at 95% confidence level. Conclusion The proposed methods are accurate, precise, simple and inexpensive. They can be applied successfully to the analysis of the two drugs in combined dosage form.